2019
DOI: 10.3892/or.2019.6973
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between C2ORF68 and HuR in human colorectal cancer

Abstract: The detailed molecular mechanisms underlying the carcinogenesis of colorectal carcinoma (CRC) remain unknown. Therefore, the present study was designed to investigate the effect of the relationship between C2ORF68 and HuR in regards to the carcinogenesis of CRC. Immunohistochemistry, immunofluorescence, flow cytometry, Transwell migration and CCK-8 assays, co-immunoprecipitation, qRT-PCR and western blot analysis were performed. The results revealed that expression of C2ORF68 was significantly upregulated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…HuR is an RNA-binding protein that recognizes U/AU-rich elements in diverse RNAs and post-transcriptionally regulates the fate of target RNAs. HuR regulates cellular responses to differentiation, senescence, inflammatory factors and immune stimuli by tightly controlling the post-transcriptional fate of specific mRNAs (33,34). HuR is expressed at high levels in a number of types of cancers and is believed to promote tumorigenesis by interacting with mRNAs encoding proteins implicated in cell proliferation and survival, angiogenesis, invasion and metastasis (23).…”
Section: Discussionmentioning
confidence: 99%
“…HuR is an RNA-binding protein that recognizes U/AU-rich elements in diverse RNAs and post-transcriptionally regulates the fate of target RNAs. HuR regulates cellular responses to differentiation, senescence, inflammatory factors and immune stimuli by tightly controlling the post-transcriptional fate of specific mRNAs (33,34). HuR is expressed at high levels in a number of types of cancers and is believed to promote tumorigenesis by interacting with mRNAs encoding proteins implicated in cell proliferation and survival, angiogenesis, invasion and metastasis (23).…”
Section: Discussionmentioning
confidence: 99%
“…The results from luciferase assay confirmed that miR-519 could directly bind to HUR mRnA and negatively regulate HUR protein expression. HUR is a RNA-binding protein that can bind and stabilize AU rich element-mRNAs (28). HUR is abundantly expressed in cancer cells and associated-malignant phenotypes (29).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al, 2008;Lukosiute-Urboniene et al, 2019). In pancreatic ductal adenocarcinoma cells, an inhibitor of apoptosis protein 1 (IAP1) expression is strongly correlated with HuR This molecular event has a synergistic effect on the onset and development of colorectal cancer (Lv et al, 2019). Recent findings have provided evidence for the relationship between HuR and exosomes.…”
Section: Rbps and Rna Stabilitymentioning
confidence: 99%
“…In colorectal cancer cells, HuR interacts with chromosome 2 open reading frame 68 (C2ORF68), which is a potential carcinogenesis‐associated factor. This molecular event has a synergistic effect on the onset and development of colorectal cancer (Lv et al, 2019). Recent findings have provided evidence for the relationship between HuR and exosomes.…”
Section: Function Of Rbps In Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation